De novo heterozygous desmoplakin mutations leading to Naxos-Carvajal disease (Swiss Medical Weekly, 2012)
STUDY/PRINCIPLES: Arrythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) is an autosomal-dominantly inherited disease caused by mutations in genes encoding desmosomal proteins and is characterised by fibrofatty replacement occurring predominantly in the right ventricle and can result in sudden cardiac death. Naxos and Carvajal syndrome, autosomal recessive forms of ARVC/D, are characterised by involvement of the right and/or left ventricle in association with palmoplantar keratoderma and woolly hair. The aim of the present study has been to screen for mutations in the desmosomal protein genes of two unrelated patients with Naxos-Carvajal syndrome. METHODS AND RESULTS: Desmosomal protein genes were screened for mutations by polymerase chain reaction as well as direct sequencing approach. In each patient we identified a single heterozygous de novo mutation in the desmoplakin gene DSP, p.Leu583Pro and p.Thr564Ile, leading to severe combined cardiac/dermatological and cardiac/dermatological/dental phenotypes. The DSP missense mutations are localised in the N terminal domain of desmoplakin. CONCLUSION: The identified variations in DSP involve highly conserved residues. Moreover, the variations are de novo mutations and they are localised in critical protein domains that appear to be mutation hot spots. We assume that these heterozygous variations are causal for the mixed Naxos-Carvajal syndrome phenotype in the screened patients.